+0  
 
0
469
1
avatar

6 2/3 x 2 2/5 x 3 3/8 =

 Sep 2, 2014

Best Answer 

 #1
avatar+3450 
+5

First, turn these numbers into inproper fractions. Here's how we'd do that:

 

$$\begin{array}{l}
6\frac{2}{3} = \frac{6\times3+2}{3}=\frac{18+2}{3}=\frac{20}{3}\\\\
2\frac{2}{5} = \frac{2\times5+2}{5}=\frac{10+2}{5}=\frac{12}{5}\\\\
3\frac{3}{8} = \frac{3\times8+3}{8}=\frac{24+3}{8}=\frac{27}{8}
\end{array}$$

 

Now we get:

 

$$\frac{20}{3}\times\frac{12}{5}\times\frac{27}{8}$$

 

This can simplified, so we get:

 

$$\frac{1}{1}\times\frac{2}{1}\times\frac{27}{1}$$

 

$$\frac{1\times2\times27}{1\times1\times1}$$

 

$$\frac{54}{1}$$

 

$$54$$

.
 Sep 3, 2014
 #1
avatar+3450 
+5
Best Answer

First, turn these numbers into inproper fractions. Here's how we'd do that:

 

$$\begin{array}{l}
6\frac{2}{3} = \frac{6\times3+2}{3}=\frac{18+2}{3}=\frac{20}{3}\\\\
2\frac{2}{5} = \frac{2\times5+2}{5}=\frac{10+2}{5}=\frac{12}{5}\\\\
3\frac{3}{8} = \frac{3\times8+3}{8}=\frac{24+3}{8}=\frac{27}{8}
\end{array}$$

 

Now we get:

 

$$\frac{20}{3}\times\frac{12}{5}\times\frac{27}{8}$$

 

This can simplified, so we get:

 

$$\frac{1}{1}\times\frac{2}{1}\times\frac{27}{1}$$

 

$$\frac{1\times2\times27}{1\times1\times1}$$

 

$$\frac{54}{1}$$

 

$$54$$

NinjaDevo Sep 3, 2014

4 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.